Analisis Penentuan Harga Jual Produk dengan Pendekatan Biaya Produksi Pada UMKM Pabrik Tahu Sarimun - Danu Harianto, Hasyim; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
This research aims to determine the calculation of tofu production costs and analyze the calculation of production costs in determining the selling price of tofu products using the product cost method. The research method used is a quantitative approach. The population in this research is the accounting journal at the tofu factory or company. The instrument in this research uses data from the factory and the results of interviews conducted with the factory owner. Data analysis in this research uses MS Excel with calculations based on the product cost method. The results of the research show that the calculation of the cost of production carried out by UMKM Tahu Bapak Sarimun still uses a simple method